Baby Party (reverse) - Unknown (Tufts Archival Research Center, 2014)
5.8 x 7.9 in., photographic print. Back of photograph showing Janet Pierce and Muriel Simonson performing in 'Baby Party,' a play produced at Tufts in 1928.